Zoom breakout room for students’ collaborative skill enhancement in history learning during Covid-19 outbreak - Agustina, Ema; Suharya, Toto (Universitas Negeri Padang, 2021)
The new transformation in history learning is needed in online learning, especially when it comes to improving students’ collaborative skills in solving problems, finding solutions, making decisions, and negotiating to achieve particular goals in 21st-century learning skills. Virtual learning rooms such as Zoom are used to ensure students’ involvement and collaboration in learning and provide opportunities for students to realize active learning with many features that can be applied. Despite many studies that have portrayed virtual learning with Zoom during the COVID-19 pandemic, fewer studies seek the utilization of Zoom Breakout Room in history learning. This study uncovered how teachers enhance students’ collaborative skills in history learning through the Zoom Breakout Room. The current study employed the qualitative approach under the case study design. In-depth interviews were directly conducted with one history teacher who was experienced in working history learning with Zoom Breakout Room to obtain the empirical data. The results showed that Teachers could use the zoom Breakout Room to improve students’ collaborative skills. In the current study, the Zoom Breakout Room, as one of the innovative tools in the Virtual Learning Environment (VLE) answered the ineffective learning with large groups in Zoom main room discussion. The breakout Room feature in Zoom itself supported an active learning process. The students are given more space to communicate in small groups and seek information, discuss, solve problems, and make collective agreements. The Zoom Breakout Room could be an alternative for teachers in facing learning challenges amid the COVID-19 outbreak.